Can Social Media Drive Tax Compliance? Insights from Muslim Generation Z, Millennials, and Sharia Perspectives - Setiawan, Ananda; Arwani, Agus (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
This study aims to test whether digital transformation using social media attributes can push towards compliance with tax regulations and provisions. This type of research is quantitative and the analysis method uses a partial least squares structural equation modelling (PLS-SEM) approach. Data were obtained from an online questionnaire of 128 respondents and processed using the Smart PLS tool. The results of the study found that tax literacy has a positive effect on tax compliance. The use of social media has a positive relationship with tax compliance, eventually, the moderation model of social media use is not able to strengthen the relationship between tax literacy and tax compliance. First, this study examines the potential for digital transformation and information disruption in the era of the industrial revolution 4.0 with social media attributes as leverage and drivers of compliance. Second, this study chose subjects in the Moslem digital generation (Muslim generation z and millennials) because they tend to be more responsive in receiving information, are drivers of innovation in the digital era, and have the potential to become taxpayers in the future.